Hemophagocytic lymphohistiocytosis triggered by Gaucher disease in a preterm neonate. (16th November 2016) - Schüller, Simone; Attarbaschi, Andishe; Berger, Angelika; Hutter, Caroline; Klebermass-Schrehof, Katrin; Steiner, Manuel
ABSTRACT: Objective: To present the diagnostic workup in an extremely low birth weight infant patient with signs of both sepsis and hemophagocytosis.Participants : A preterm infant presented with clinical and laboratory signs of early-onset sepsis including hepatosplenomegaly, thrombocytopenia, direct hyperbilirubinemia, and elevated liver enzymes.Methods : Despite extensive septic workup, no underlying infection was detected. Additional hyperferritinemia and other elevated inflammatory parameters raised the suspicion of a primary or secondary hemophagocytic lymphohistiocytosis (HLH).Results: However, further metabolic analysis yielded a positive result for Gaucher disease (GD) type 2, a rare, but possible trigger of HLH.Conclusions : Our case shows that GD may lead to the picture of a secondary HLH and that a metabolic workup should always be performed in patients in whom primary HLH has been excluded.